STUDI TUMBUHAN BERKHASIAT OBAT PADA SUKU KAILI DA’A KECAMATAN KINOVARO KABUPATEN SIGI SULAWESI TENGAH - Sri Rizqi Muthmainnah; Nurlina Ibrahim; Ririen Hardani (Biocelebes, 2018)
Study of medicinal plants on Kaili Da’a tribe at Kinovaro district, Sigi Regency in Central Sulawesi has been done to preserve the knowledge and use of herbs for traditional medicine. This study aims to determine the type of plants used as medicine, the type of disease being treated as well as how to use these plants by Da'a tribe. This research is a descriptive study using qualitative methods with a sampling technique that snowball sampling through interviews and direct observation of 7 respondents of Kaili Da'a tribe. Based on the interview, known as much as 31 families of medicinal plants. The results of identification of the plants used as medicines known 65 species, 6 species which have been unidentified its species (2 species unidentified families). The most widely used plant is from Euphorbiaceae family (6 species). Parts of plants used include leaves, stems, fruits, roots, herbs, seeds, sap and flowers. The leaves are part of plants that have the highest usage percentage (77%). As for how to use of medicinal plants is done by mouth, chewed, spilled, smeared, taped, wrapped, dyed and used in massage. How to use the most that drunk as much as 70%.